Algunas cuestiones de la formación del participio en español y portugués - Krekovics, Diana (Acta Hispanica, 2009)
The aim of this paper is a historical-comparative presentation of the development of past participle forms in the Iberoromanic languages. First of all, we focus on the Latin forms with desinence -utus which have gradually disappeared in those languages that are spoken in the Iberian Peninsula. After a rapid glance over the formation of participles in the languages in question (Spanish, Catalan, Portuguese) we make comparison with the help of statistical datas that were obtained from Spanish and Portuguese literary and legal texts, written in the 13th, 14th and 15th centuries. The subject of this comparison is the incidence rate in the aforementioned centuries and genres of those Spanish and Portuguese past participles that earlier had the desinence - utus in Latin.